Mapping the Potential of the Economic Sector of Kediri Regency - Sishadiyati Sishadiyati; Taufik Taufik (Journal of Economics, Business, and Government Challenges, 2022)
The purpose of this study is to find out the mapping of the potential of the economic sector of Kediri Regency. The type of data used is secondary data with quantient Dynamic Location Analysis (DLQ) analysis methods and Klassen Typology. The results of this study concluded that the economic sectors that fall into the category of advanced and fast-growing (type I), namely: 1) the agricultural, forestry, and fisheries sectors; and 2) information and communication. While the economic sectors that fall into the category of lagging (type IV), namely: 1) mining and quarrying; 2) provision of accommodation and drinking meals; and 3) company services. While the potential economic sectors in the future, namely: 1) Agriculture; 2) Mining; 3) Industry; 4) Procurement; 5) Water Procurement; 6) Transportation; 7) Provision of Accommodation; 8) Information; 9) Financial Services; 10) Real Estate; 11) Company Services; 12) Administration of Government; 13) Educational Services; and 14) Other services. While the economic sectors that fall into the category are not potential, including: 1) Construction; 2) Trading; and 3) health care.